2012
DOI: 10.1111/neup.12005
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus‐associated primary central nervous system cytotoxic T‐cell lymphoma

Abstract: Primary central nervous system lymphoma (PCNSL) expressing T-cell markers is rare, among which nasal-type extranodal NK/T-cell lymphoma is an extremely rare subtype associated with Epstein-Barr virus (EBV) infection. Here we report the clinicopathologic features of a case of EBV-associated PCNSL showing a cytotoxic T-cell phenotype. The patient, a 73-year-old woman, presented with rapidly progressive mental deterioration. Brain MRI revealed multiple lesions with swelling in the bilateral cerebral hemispheres, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Histopathological examination was performed on 4‐μm‐thick sections stained with HE. The paraffin‐embedded sections were processed for immunohistochemistry using methods previously described . Primary monoclonal antibodies against the following antigens were used: human IDH1 R132H (clone H09; Dianova, Hamburg, Germany; dilution 1:100), MGMT (clone MT3.1; Chemicon International, Temecula, CA, USA; 1:50), and human p53 (clone DO‐7; Dako, Glostrup, Denmark; 1:50).…”
Section: Methodsmentioning
confidence: 99%
“…Histopathological examination was performed on 4‐μm‐thick sections stained with HE. The paraffin‐embedded sections were processed for immunohistochemistry using methods previously described . Primary monoclonal antibodies against the following antigens were used: human IDH1 R132H (clone H09; Dianova, Hamburg, Germany; dilution 1:100), MGMT (clone MT3.1; Chemicon International, Temecula, CA, USA; 1:50), and human p53 (clone DO‐7; Dako, Glostrup, Denmark; 1:50).…”
Section: Methodsmentioning
confidence: 99%
“…The detection of cytoplasmic granuleassociated proteins, such as granzyme B and perforin, indicated that this T-cell lymphoma had a cytotoxic phenotype. To our knowledge, only a few previous cases of primary CNS cytotoxic T-cell lymphoma have been reported (6,7). This is a rare phenotype that may be associated with more pronounced necrosis and infiltration of macrophages than lymphoma cells.…”
Section: Discussionmentioning
confidence: 95%
“…A total of 10 cases were collected from case reports in the English language literature (Table ) and analysed . There were nine IC cases and one IS case that was infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…according to the 2008 World Health Organization (WHO) classification . Moreover, published case reports were reviewed, and 10 additional cases were selected for further analysis . The clinical and pathological information was obtained from a review of the papers.…”
Section: Methodsmentioning
confidence: 99%